Assessment Instrument of Student Character Observation - Jetty F. Kaunang; Hantje Ponto (Journal of International Conference Proceedings (JICP), 2020)
Behavior is an action that describes the human character in socializing with the community environment. Human good and bad actions have an impact on the comfort of others. This depends on the behavior that exists in each individual. The character of students can be formed through the learning process at school by directing the behavior in accordance with universally applicable norms. Formation of character by directing positive behavior needs to be done from an early age, especially when getting education at the level of primary education (primary school). Student behavior can be assessed by using an observation assessment instrument to obtain accurate data about student behavior or behavior during the learning process. Based on these assessments the teacher can provide guidance to direct the behavior so that the character of students is formed in accordance with applicable norms. This instrument model is to make it easier for teachers to observe student behavior at school so that later remedies are documented.